2017
DOI: 10.1186/s12879-017-2757-2
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-acquired infections of Salmonella enterica serotype Typhi in South Africa: phenotypic and genotypic analysis of isolates

Abstract: BackgroundWorkers in clinical microbiology laboratories are exposed to a variety of pathogenic microorganisms. Salmonella species is among the most commonly reported bacterial causes of laboratory-acquired infections. We report on three cases of laboratory-acquired Salmonella enterica serotype Typhi (Salmonella Typhi) infection which occurred over the period 2012 to 2016 in South Africa.MethodsLaboratory investigation included phenotypic and genotypic characterization of isolates. Phenotypic analysis included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 24 publications
9
32
0
1
Order By: Relevance
“…Some of the main factors useful in the prediction of real infection are: 1) similar strains being isolated repeatedly during course of an infection after the isolation of a strain in pure culture from the infected site, 2) in bloodstream infections, patients should have clinical evidence of the infection with one positive blood culture or only two positive CoNS blood cultures within 5 days, and 3) if CoNS is isolated from a skin or soft tissue bacterial culture of a suspected infectious lesion, the isolated organism should be proposed as a pathogen and suitable treatment should be initiated. [35][36][37] Among different-tested antibiotics, the results of our study have revealed that linezolid and vancomycin are effective antibiotics against S. aureus and Enterococcus spp, which was in agreement with the rates reported by Dharmapalan et al from India, 38 He et al from China, 39 Lei Tian et al from China, 40 and Al-Naqshbandi et al from Iraq. 41 However, the results of several studies were not consistent with our research and it has been reported that the resistance to vancomycin is high.…”
Section: Discussionsupporting
confidence: 92%
“…Some of the main factors useful in the prediction of real infection are: 1) similar strains being isolated repeatedly during course of an infection after the isolation of a strain in pure culture from the infected site, 2) in bloodstream infections, patients should have clinical evidence of the infection with one positive blood culture or only two positive CoNS blood cultures within 5 days, and 3) if CoNS is isolated from a skin or soft tissue bacterial culture of a suspected infectious lesion, the isolated organism should be proposed as a pathogen and suitable treatment should be initiated. [35][36][37] Among different-tested antibiotics, the results of our study have revealed that linezolid and vancomycin are effective antibiotics against S. aureus and Enterococcus spp, which was in agreement with the rates reported by Dharmapalan et al from India, 38 He et al from China, 39 Lei Tian et al from China, 40 and Al-Naqshbandi et al from Iraq. 41 However, the results of several studies were not consistent with our research and it has been reported that the resistance to vancomycin is high.…”
Section: Discussionsupporting
confidence: 92%
“…Findings from several studies have shown that PCT has been advocated as a preferable biomarker for diagnosis and differential diagnosis of bacterial infections, displaying severity of bacterial infection and activity of inflammation 1721. Moreover, PCT might assist physicians in making decisions on antibiotic therapy for infectious diseases 2224. The ProVAP trial and the PRORAT trial suggested: 1) PCT<0.5 μg/L or a decrease by >80%, antibiotic discontinuation was encouraged; 2) PCT<0.25 μg/L or a suggested decrease by >90%, antibiotic discontinuation was strongly encouraged 9,25,26.…”
Section: Discussionmentioning
confidence: 99%
“…It is imperative that vaccination of children depends on the mothers or parent's knowledge and attitude. 30,31 The study revealed that mothers knowledge is an important component for childhood immunization (p < .05). It was estimated that 57.5% of mothers have good knowledge about the vaccination program in Malaysia.…”
Section: Knowledge Of Mothers On Childhood Vaccinationmentioning
confidence: 97%